Morphological and mechanical properties of lower limbs in competitive racewalkers: Associations with performance. (2nd December 2021) - Walker, Josh; Nicholson, Gareth; Hanley, Brian
Abstract: Racewalking is an unconventional form of competitive gait that elicits a unique loading profile on lower limb muscles and tendons. This study mapped the structural and mechanical properties of lower limbs in competitive racewalkers and made associations with World Athletics competition performance points. Fourteen international racewalkers (seven men, seven women) were recruited for this study. Static ultrasonography was used to quantify muscle and tendon morphological characteristics. An isokinetic dynamometer was used to measure passive musculotendinous stiffness of the triceps surae, isometric (seven knee/ankle angle combinations) and isokinetic (four angular velocities) strength parameters in the plantarflexors and dorsiflexors, and isokinetic knee flexion and extension strength at five angular velocities. Correlations were found between performance and fascicle length of gastrocnemius medialis ( r = –0.569, p = 0.034), dorsiflexor strength at 120°/s ( r = 0.649, p = 0.016) and knee flexor strength at 30°/s ( r = 0.632, p = 0.020). No associations were found for isometric plantarflexion or passive stiffness properties. Overall, the study showed various morphological and mechanical properties are associated with performance in competitive racewalkers. These associations seem to be related to the specific and unique biomechanical characteristics of racewalking.